Global Civil Society Movements in the Philippines - Pedro Jr., Antonio C. (Kasarinlan: Philippine Journal of Third World Studies, 2015)
Review of Global Civil Society Movements in the Philippines edited by Teresa S. Encarnacion Tadem (Mandaluyong City: Anvil Publishing, Inc.)